Reflections on Religious Life in the Novel Ahlul Kahfi: A Mimetic Analysis - Attuqo, Sanja Mukhlis Jazuli (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aimed to analyze the reflection of religious life in the novel Ahlul Kahfi using a mimetic approach. Literature is not only an artistic expression but also a representation of reality, including religious values. This research employed a qualitative descriptive method with a textual analysis approach. The data were collected through documentation and literature study, focusing on dialogues, narration, and plot elements that reflect religious values. The findings revealed that the novel contains strong religious values such as faith, patience, and reliance on God, which are portrayed through characters and conflicts. The discussion showed that, through the mimetic approach, the novel reflects real human experiences in maintaining faith under social pressure. The study concluded that Ahlul Kahfi successfully represents religious life and serves as a medium for moral and spiritual reflection.